Nomogram for predicting the distal adding-on phenomenon in severe and rigid scoliosis - Li, Zhongyang; Yang, Huiliang; Zhou, Chunguang; Xiu, Peng; Yang, Xi; Wang, Lei; Feng, Ganjun; Liu, Limin; Song, Yueming (Frontiers in Surgery, 2023)
Background The distal adding-on phenomenon has attracted extensive discussion in the field of spine surgery due to the continual occurrence after scoliosis correction. Previous work has mainly focused on adolescent idiopathic scoliosis (AIS), and a relatively high number of theories for the mechanism of the distal adding-on phenomenon has been proposed for these kinds of patients. Severe and rigid scoliosis, as a special disease form, has a unique etiology, clinical manifestations and internal mechanisms distinct from those of AIS. Given the uniqueness of this disease, the mechanism and causes of the distal adding-on phenomenon have been infrequently studied in depth. Objective To define clinical and radiological factors associated with distal adding-on in patients with severe and rigid scoliosis. Methods Radiographic parameters and demographic data of patients with severe and rigid scoliosis were evaluated preoperatively, after posterior instrumentation and fusion surgery, and at the final follow-up via radiographs. According to the appearance of distal adding-on at the final follow-up, the patients were grouped into the Adding-on and the Non-adding-on groups. Various radiological parameters were analyzed in stepwise multivariate logistic regression to identify the variables associated with distal adding-on, which were then incorporated into a nomogram. The predictive performance and calibration of the nomograms for distal adding-on were assessed using C statistics and calibration plots. Results 93 patients (21 in the Adding-on and 72 in the Non-adding-on group) were included. The incidence of distal adding-on was 22.6%. The variables associated with distal adding-on were the anterior release, posterior internal distraction, and later posterior spinal fusion (IP) procedure, the posterior vertebral column resection and posterior spinal fusion (PVCR) procedure, postoperative apical vertebral translation (Post-AVT) and preoperative slope of the line linking the pedicles on the concave side of the upper- and lower-end vertebrae (Tan α). Combining these factors, the nomogram achieved a concordance index of 0.92 in predicting distal adding-on and had well-fitted calibration curves. Conclusions For patient with a negative Tanα in severe and rigid scoliosis, the risk of distal adding-on tended to increase, and it is recommended to give priority to IP or PVCR. In the final correction, a smaller Post-AVT should not be pursued excessively.